PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PENCERNAAN MANUSIA - Mutmainna; Sativani Hayati, Riza; Hambali, Hilmi (Jurnal Biogenerasi, 2025)
This study aims to develop a Problem-Based Learning (PBL)-based e-module on the human digestive system and determine its practicality. This research is a research and development (R&D) study using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed e-module was validated by two expert validators and tested for practicality by teachers and 11th-grade students of SMA YAPIP Makassar. The validation results showed that the e-module was categorized as very valid, with percentages of 93% and 98%, respectively. The practicality test results for teachers were 87% (practical category), and for students, 83% (practical category). This e-module incorporates PBL learning syntax, is complemented by images, videos, a glossary, and an assessment rubric, and is flexibly accessible to both teachers and students. Based on these results, it can be concluded that the developed PBL-based e-module on the human digestive system is practical and suitable for use in the learning process.